Penggunaan Gambar Luas Daerah Untuk Meningkatkan Pemahaman Siswa Terhadap Operasi Penjumlahan Bilangan Pecahan SD Kabupaten Bone - Iriani Sidji (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
The purpose of this research is to increase the understanding in summing the fractions by using the wide picture of the fourth grade student area of SD Negeri 9 Ta '. Types of action research with cycles include planning, execution, observation, and reflection. Research data is activity data and student learning result in addition of fraction. Data obtained by observation, test, field notes. The result of this research is in cycle I (1) study at the stage of percentage in mempragakan image area not maximal yet (2) students have difficulties in adding fraction (3) group work not yet maximal, meanwhile in cycle II has significant increase that is (1 ) presentation at the presentation stage of the picture of the width of the area has been maximally run in accordance with the plan (2) the students are happy to do the sum of the fractions by using the broad area picture (3) the students can present the rare of fractional disappearance using the area wide image, can be seen in cycle I less qualification (K), cycle II qualification good (B). Means by using the image area in the fractional learning can improve student learning outcomes fourth grade SD Negeri 9 Ta '.